The effect of KDEL and PPI genes co-expression on the anti-toxoplasma scFV activity in TRANSGENIC Nicotiana tabacum cultivar SR1 / Fatin Iffah Rasyiqah Mohamad Zoolkefli - Fatin Iffah Rasyiqah , Mohamad Zoolkefli (2018)
Toxoplasmosis is a disease caused by infection of a parasitic protozoan known as Toxoplasma gondii, which has economic implications due to neonatal loss and abortion in livestock animals. In human adults, it is usually asymptomatic but can cause complications in immunocompromised persons and pregnant women which leads to congenital effects on newborn babies. As a therapeutic approach to combat the disease, biopharmaceutical products, such as recombinant antibody targeting to T. gondii tachyzoite, has been introduced as an alternative to drugs and vaccines. Innovative approaches for the expression and production of these novel biopharmaceutical products which increased complexity towards disease targets have been the subject of recent investigations. Plants have now emerged as a preferred host to express and produce these recombinant proteins as it provides advantages in term of efficiency, cost, scalability, safety and compatibility as compared to prokaryotes and mammalian cell lines. Thus, in this study, the target antibody, an anti-Toxoplasma scFv encoded by the TP60 gene was transformed into leaf explants of Nicotiana tabacum cv. SR1 using Agrobacterium tumefaciens strain LBA4404. The constructs were transformed in a series of experiments in tandem with different enhancer elements comprising proteinase inhibitors or a KDEL retention sequence or combinations of both elements in order to assess their ability to stabilize and enhance the scFv production. Two different proteinase inhibitors that have been used in this study were Oryzacystatin inhibitor (OCPI) (a cysteine inhibitor) and Bowman-Birk inhibitor (BBI) (a trypsin and chymotrypsin inhibitors). β-glucuronidase (GUS) and green fluorescence protein (GFP) assays as well as PCR results confirmed the presence of transgenes in the tobacco genome that was stably inherited into T1 generation. For Western blot analysis, the selected lines of transgenic tobacco plants transformed with pTP60 construct in combination with BBI-KDEL (pTP60BBIKDEL) elements was found to produce the highest anti-Toxoplasma scFv recombinant antibody accumulation at the expected size of ~ 54 kDa (homodimer formation) which was at first observed at ~ 27 kDa (monomer) in T0 tobacco plants. No expression was detected in non-transformed plants. The results were also confirmed at the mRNA level using real-time PCR analysis with the BBI-KDEL tandem constructs expressing TP60 gene approximately 19-fold higher as compared to plants transformed with the pTP60 construct in the absence of any proteinase inhibitor and/or KDEL. Interestingly, the introduction of all of these elements did not or only negligibly affected the growth and development of the transgenic tobacco plants as compared to the wild-type. Our results confirmed the ability of plants to function as bio-factories for recombinant protein production and showed that the use of proteinase inhibitor and KDEL elements may be useful in improving the yield of the targeted antibody proteins.